How do you solve #4 (c - 1) = - 6 (c+2) + 2c#?
c = -1
The first step is to distribute the brackets.
hence: 4c - 4 = -6c - 12 +2c
Now collect the terms in c to the left side and collect numeric terms on the right.
Note that when we move terms from one side of an equation to the other we 'reverse' their operation.
So addition becomes subtraction and vice-versa.
Consider the arithmetic equation 4 + 3 = 7 which we can express as
4 = 7 - 3 noting that + 3 on the left becomes - 3 on the right. This also applies to algebraic terms.
collecting terms gives: 8c = - 8
divide both sides by 8 to obtain c.